Optimasi Proses Produksi Bioplastik Poli (3-Hidroksibutirat) dengan Bakteri Bacillus Sp Faac 20801 Menggunakan Bahan Dasar Jerami Padi Secara Fermentasi - Krisyanella, Krisyanella; Djamaan, Akmal; Aulia, Witra (Jurnal Sains dan Teknologi Farmasi, 2012)
Optimization of a production of a bioplastic poly (3 - hidroxybutirat) (P(3HB) by fermentation using Bacillus sp FAAC 20801 bacteria and rice straw as carbon source has been carried out. Detection of P(3HB) was done using gas chromatography. The highest glucose level obtain by using H2SO4 5% for hydrolisis. 46,800 mg straw (glucose concentration 200 mg/ml) were obtained 5,379 mg biomass and 0.058 mg P(3HB) ; from 83,400 mg rice straw (glucose concentration 400 mg/ml) were obtained 5,011 mg biomass and 0.124 mg P(3HB) ; from 142,800 mg rice straw (glucose concentration 600 mg/ml) were obtained 3,992 mg biomass and 2.309 mg P(3HB).